Convenient Novel Method for Diagnosing Diastolic Dysfunction: Electrocardiographic Diastolic Index - Murat Oğuz Özilhan; Özge Çakmak Karaaslan; Cem Çöteli; Orhan Maden (International Journal of the Cardiovascular Academy, 2023)

(untitled)
Background and Aim:Left ventricular diastolic dysfunction (LVDD) is the primary pathophysiology in patients with preserved ejection heart failure. Hypertension (HT) results in myocardial structural changes and accelerates the progression to LVDD. Electrocardiographic diastolic index (EDI) calculated from electrocardiogram parameters can provide information about the correlation between hypertrophy of the left ventricle and LVDD. We investigated the predictor of EDI in detecting LVDD in patients followed up with HT.Materials and Methods:This study included 202 consecutive patients with HT between January 2022 and March 2022. The patients were classified without and with LVDD. The EDI is created as (V5-R amplitude + V1-S amplitude x aVL-R amplitude/PWL-I amplitude). The prediction value of the EDI for LVDD was evaluated by curve analysis of the receiver operating curve. Multivariate and univariate logistic regression analyzes were used to evaluate the free predictors of LVDD. Two multivariate models were used (model I: EDI as a continuous variable and model II: EDI as a categorical variable).Results:The patients were classified into two groups by showing LVDD. The average age of the study population was 50 ± 14 years, and 57.4% of the patients were female. The patient EDI value was 8.5 ± 7.3. The EDI value of the first group was remarkably lower than that of the second group. When the limit value of EDI is greater than 7.4 mV, it predicts LVDD with 63.6% sensitivity and 79.8% specificity. In univariate logistic regression analysis, the presence of LVDD was associated with EDI. Two different multivariate regression models were constructed to evaluate EDI as both a continuous variable and a categorical variable. EDI was determined as an independent predictor of LVDD in both models.Conclusion:The EDI is an essential assessment tool in predicting DD in patients who are followed up with HT because it is a cheap, accessible, and easy-to-use formula.